2009
DOI: 10.1002/ejoc.200900766
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Ferrocenyl‐Based P,S Ligands (ThioClickFerrophos) and Their Use in Pd‐Catalyzed Asymmetric Allylic Substitutions

Abstract: A series of P,S ligands (ThioClickFerrophos) based on a triazoleferrocenylethyl backbone were synthesized in a fourstep sequence by click chemistry methodology. The new P,S ligands were applied in allylic alkylations, etherifications, and aminations of 1,3-diphenylprop-2-enyl acetate catalyzed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…The synthesis of thioclickferrophos (TCFP) ligand involved the same strategy as clickferrophos, by which the lithiated ferro- cenyl triazole moiety was quenched with various disulfides to achieve a family of thioclickferrophos ligands (Scheme 29). [38] The TCFP ligands were studied for their catalytic activity and asymmetric induction on the same set of reactions as CFP ligands to compare the efficiency of the catalysts. Ligands 76 a-f were screened for the alkylation of allyl acetate with [{PdA C H T U N G T R E N N U N G (h 3 -C 3 H 5 )Cl} 2 ].…”
Section: Thioclickferrophosmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of thioclickferrophos (TCFP) ligand involved the same strategy as clickferrophos, by which the lithiated ferro- cenyl triazole moiety was quenched with various disulfides to achieve a family of thioclickferrophos ligands (Scheme 29). [38] The TCFP ligands were studied for their catalytic activity and asymmetric induction on the same set of reactions as CFP ligands to compare the efficiency of the catalysts. Ligands 76 a-f were screened for the alkylation of allyl acetate with [{PdA C H T U N G T R E N N U N G (h 3 -C 3 H 5 )Cl} 2 ].…”
Section: Thioclickferrophosmentioning
confidence: 99%
“…Similarly, an asymmetric amination reaction under the same conditions resulted in 66 % ee (Scheme 31). [38] Then thioclickferrophos was employed in the 1,3-dipolar cycloaddition of N-benzylidineglycinate and a-enones and other dipolarophiles. An earlier report by Fukuzawa et al demonstrated an exo selectivity when a combination of Cu I and clickferrophos were used.…”
Section: Thioclickferrophosmentioning
confidence: 99%
See 1 more Smart Citation
“…A maximal ee of 90% was recorded in standard AAA reactions [120]. Chan and co-workers also altered their design of L81-L83 and came up with ligand L85, where the phosphorus and sulfur atoms were separated by four A sugar-based P-S ligand L86 has been developed by Khiar and co-workers (Fig.…”
Section: P-s Ligandsmentioning
confidence: 99%
“…[7] However, the corresponding protocols for the synthesis of fully substituted 1,2,3-triazoles via Huisgen reaction remain a challenge [8] due to the increased energy barrier (270 kJ mol -1 ), [9] particularly for the synthesis of 5-thio-1,2,3-triazoles. 1,2,3-Triazoles bearing a 5-sulfur substituent represent to be a series of useful molecules, [10] for example, using as an excellent chiral ligand in organic synthesis [11] and potential antifungal agents. [12] Recently, Ding reported a method of Iridium-catalyzed cycloaddition of thioalkynes with azide [13] .…”
Section: Introductionmentioning
confidence: 99%